THE STUDENTSâ PROBLEMS IN WRITING COMPOUND COMPLEX SENTENCE AT ENGLISH DEPARTMENT LAMBUNG MANGKURAT UNIVERSITY BATCH 2014 - Azidin, Noor Azrina (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
This paper studied the problem of writing compound-complex sentence by English department students this study also describes the problems that students faced in writing compound-complex sentence and the data are collected from the student of English Department batch 2014. This study used descriptive-qualitative research in order to find out and describe the studentsâ problem in writing a compound-complex sentence. Moreover, the researcher used written test as the instrument and also used simple random sampling technique in selecting the subjects of the study. Therefore, 40 students from English Department batch 2014 had been chosen to be the subjects. Finally, the researcher used descriptive method to describe the problems that the researcher found and then explained the problems in the discussion part based on the data in the first test and the second test. The research results showed that there are three problems that the students faced in writing the compound-complex sentence. The major is in the conjunction. It happened because the students have difficulties in choosing the conjunctions that are usually used in writing compound-complex sentences. The second major problem is the punctuation. It happened because they forget to put the punctuation or they put the punctuation in the wrong place. The minor problem is the less known about the compound-complex sentence. The less knowledge here means the students already know about compound complex but the subjects still have difficulties in choosing the conjunction and the punctuation.